Joyful Learning dalam Pendidikan Rasulullah SAW - Robingun Suyud El Syam; Hidayatu Munawaroh; Novida Aprilina Nisa Fitri (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2023)
This article aims to present joyful learning inthe education of Rasulullah SAW. The research uses library research, is presented in a narrative manner, and is analyzed descriptively. The results of the study showed that the Prophet Muhammad had practiced joyful learning in his learning process, where he played and joked with young children, while guiding and reminding them when they made mistakes, and motivating them to do good. The principle of learning is by prioritizing gentle, humble, not neglecting, and polite speech. The implication of the research is that it can help educators and stakeholders to use fun learning strategies in Rasulullah SAW education effectively for Islamic education, especially early childhood.